The impact of a change in monetary policy by means of a monetary macro-econometric model - De Jager, Shaun (University of the Free State, 2001)
Monetary policy essentially reflects monetary theory. As the financial system is complex and intricate in nature, it becomes virtually impossible to conceive without a theory to simplify its structure. This simplified structure should ideally be geared towards the generation of a transparent financial environment in order to enhance the effectiveness of monetary policy initiatives. To this end, a new monetary policy framework was adopted by the SARB in the year 2000, and is based on achieving a pre-determined inflation target over a specific period of time. The mission of the SARB to protect the value of the domestic currency hence remains the primary objective of the monetary authorities, and any assistance in increasing the transparency of the Bank's monetary policy initiatives will no doubt increase the overall effectiveness of monetary policy. Inflation basically remains a monetary phenomenon and the rates of growth in domestic money supply and bank credit extension are important factors in the new inflation targeting environment. Accordingly, the Bank's actions are aimed at adjusting the repo rate to influence economic expansion and the demand for credit. It is essentially for this purpose that the monetary macro-econometric model has been estimated in this study, and furthermore to elucidate the links between the financial and real sectors of the economy. The model has been structured to reflect money demand theory and how the various domestic economic agents interactively react to a monetary policy impulse. Various alternative monetary policy simulations were performed on the model to determine if the model was robust, and whether it suitably reflected the intricate links between the various key sectors of the economy. The results of the model suggested that it was stable and suitable for policy simulation purposes, and that the monetary transmission mechanism in South Africa is fairly long. In addition, it was found that there was a close relationship between real economic activity and inflation, while the lagged impact on real output growth from a hypothetical change in interest rates was approximately one year. The primary objective of the newly adopted inflation targeting framework is to achieve price and financial market stability over the long-term. As this framework is of a forward-looking nature, it becomes imperative to realise that monetary policy initiatives taken now, will result in (or influence) the possible outcome of the future. This process will even more importantly determine whether the SARB will achieve its inflation target or not. However, the sole purpose of this study was to develop a model that suitably illustrates the key links in the transmission mechanism, and not specifically to determine a model geared towards forecasting the future rate of inflation. The structure and theoretical foundation of the model is not a guarantee for successful monetary policy implementation, but its importance in illustrating the links between the key sectors of the economy cannot be denied. This characteristic makes the model a useful tool in the wide arsenal of operational instruments at the Bank's disposal, and in the process induces an environment in which the monetary policy implementation process becomes more transparent. Afterall, it is the credibility and transparency of the monetary authority that enhances the various stake holders ability to interpret the signalling intentions of the central bank, and it is this that ultimately determines the effectiveness of monetary policy.
Dissertation (M.Com. (Economics))--University of the Free State, 2001
Keywords: Monetary policy -- Decision making; Fiscal policy -- South Africa